Introduction to microbiology - Burnside, Dale; Shallua, Lucas D. (Microbiology series (Minnay), 2008)
This DVD introduces the field of microbiology and discusses the importance of microorganisms not only as causative agents of disease but also as important contributors to food production, antibiotic manufacture, vaccine development, and environmental management. It presents a brief history of the science of microbiology, an overview of the microbial world, a discussion of the scope and relevance of microbiology in today’s society, and predictions about the future of microbiology.